Effect of lithium borate coating on the electrochemical properties of LiCoO2 electrode for lithium-ion batteries - Victor D. Zhuravlev (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2020)
The effect of a protective coating of fused lithium borate, Li3BO3, on the physicochemical and electrochemical characteristics of LiCoO2 has been studied. A cathode material produced by the SCS method using binary organic fuel, glycine and citric acid. The influence of the experiment conditions on the morphology, crystal structure and specific surface of lithium cobaltite was studied. Electrochemical testing of LiCoO2∙nLi3BO3 samples, n = 5 and 7 mass %, has been performed in the cathode Li|Li+-electrolyte|LiCoO2∙nLi3BO3 half-cell using 1M LiPF6 in EC/DMC mixture (1:1) as electrolyte in the 2.7-4.3 V range at normalized discharge current С/10, С/5, С/2. The maximal initial discharge capacity of 185 mAh/g was detected for the samples with 5 mass % Li3BO3. The coulomb efficiency of optimal materials in the 40th cycle was 99.1%.